2014
DOI: 10.2458/56.16514
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Carbon Fraction of Biogas and Natural Gas Fuel Mixtures Determined with14C

Abstract: This study investigates the accuracy of the radiocarbon-based calculation of the biogenic carbon fraction for different biogas and biofossil gas mixtures. The focus is on the uncertainty in the 14 C reference values for 100% biogenic carbon and on the 13 C-based isotope fractionation correction of the measured 14 C values. The separately (AMS) measured CO 2 and CH 4 fractions of 8 different biogas samples showed 14 C values between 102‰ and 116% (pMC). The δ 13 C values of these samples varied between -6‰ and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 39 publications
(67 reference statements)
1
37
0
1
Order By: Relevance
“…The radiocarbon signature of DOC was measured following extraction and purification at the A.E. Lalonde AMS facility (University of Toronto) using a 3MV tandem accelerator mass spectrometer (High Voltage Engineering) following established methodologies (Lang et al, 2016;Palstra and Meijer, 2014;Zhou et al, 2015), and is reported with an error estimate of 1σ .…”
Section: Laboratory Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The radiocarbon signature of DOC was measured following extraction and purification at the A.E. Lalonde AMS facility (University of Toronto) using a 3MV tandem accelerator mass spectrometer (High Voltage Engineering) following established methodologies (Lang et al, 2016;Palstra and Meijer, 2014;Zhou et al, 2015), and is reported with an error estimate of 1σ .…”
Section: Laboratory Analysesmentioning
confidence: 99%
“…Statistical analyses were completed in R version 3.1.3 (R Core Team, 2015) using the packages "nlme" (Pinheiro et al, 2015), "lmtest" (Zeileis and Hothorn, 2002), "lmSupport" (Curtin, 2015), "car" (Fox and Weisberg, 2011), and "zoo" (Zeileis and Grothendieck, 2005). The effect of slumping on stream chemistry and optical characteristics was assessed using linear mixed-effects models in the "nlme" package of R. For each parameter, analyses were split into two separate models that included data for upstream and downstream chemistry and upstream and within-slump chemistry.…”
Section: Statistical Analyses and Calculationsmentioning
confidence: 99%
“…(1), expresses the 14 C content in the analysed material as refereed to a standard (IAEA C6 in our case) corrected for background, isotopic mass fractionation and for the radioactive decay of the calibration material e k t 0 Àts ð Þ term À Á . A detailed discussion about the use of the previous formula is also report in [23].…”
Section: Methodsmentioning
confidence: 98%
“…Em estudos de fração biogênica de polímeros e combustíveis (Jou et al 2015, Palstra & Meijer 2014, por exemplo, não é necessário calibrar os resultados, mas sim determinar o percentual de carbono biogênico a partir do resultado de "fração moderna" (Stuiver & Polach 1977) fornecido pelo laboratório. Na maior parte das aplicações, no entanto, é fundamental proceder à calibração das idades de radiocarbono utilizando a curva apropriada.…”
Section: Idades Calibradasunclassified